Synchronization Quality Analysis with Consideration of High Cumulants of Phase Error Distribution - Bondarev, A.; Lazko, O.; Nedostup, L. (Elektronika ir Elektrotechnika, 2006)
Presented calculations have shown that high order cumulants consideration of phase error distribution in the synchronization system gives an opportunity to refine accuracy of synchronization quality estimation. Advantages of described simplified approach over precise method are definite decreased calculation expenses, possibility of analysis of transient process of phase error statistical characteristics determination, possibility of simultaneously consideration of noise and internal or external interference influence. Development of these advantages provide opportunities for further application of described analysis technique. Ill. 3, bibl. 5 (in English; summaries in English, Russian and Lithuanian).